2018
DOI: 10.5114/pm.2018.77308
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of systemic lupus erythematosus without and with antiphospholipid syndrome in peri- and postmenopausal age

Abstract: Antiphospholipid syndrome (APS) in patients with systemic lupus erythematosus (SLE) displays a severe disease sub-phenotype with vascular manifestations ranging from peripheral thrombosis to neurologic and ophthalmic symptoms. The prevalence of morbidities including thrombosis, renal lesions, and cognitive impairment contributes to a higher risk of organ damage and a reduced quality of life in patients. In addition to the clinical heterogeneity, the diagnostic challenge is heightened in elderly patients as APS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…This finding is consistent with previous studies that also found that secondary antiphospholipid syndrome was mainly associated with SLE. [17][18][19] Furthermore, the most common comorbid disease in our patients was hypothyroidism; this finding is consistent with previous studies that detected a high prevalence of autoimmune thyroiditis and hypothyroidism in SLE patients. 20,21 In our survey, patients who had hypothyroidism presented with lower constitutional symptoms such as fatigue and fever, autoimmune hepatitis, depression, headache and hypertension.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with previous studies that also found that secondary antiphospholipid syndrome was mainly associated with SLE. [17][18][19] Furthermore, the most common comorbid disease in our patients was hypothyroidism; this finding is consistent with previous studies that detected a high prevalence of autoimmune thyroiditis and hypothyroidism in SLE patients. 20,21 In our survey, patients who had hypothyroidism presented with lower constitutional symptoms such as fatigue and fever, autoimmune hepatitis, depression, headache and hypertension.…”
Section: Discussionsupporting
confidence: 93%
“…68 More evaluation is needed regarding the impact of HT use on risk and severity of autoimmune conditions such as systemic lupus erythematosus (SLE) or rheumatoid arthritis (RA), but those with antiphospholipid syndrome, a hypercoagulable state associated with SLE, should avoid HT. 69,70 Formulations and Approach to Prescribing…”
Section: Other Common Conditionsmentioning
confidence: 99%
“…In patients with systemic lupus erythematosus, the risk–benefit ratio of MHT must be weighed carefully due to the increased risk of VTE, cardiovascular events, and disease flare. 68 Conversely, as rheumatoid arthritis is a risk factor for osteoporosis, its presence may be an added consideration in symptomatic women who are candidates for MHT.…”
Section: Special Situationsmentioning
confidence: 99%